Effect of variation of liquid condition on transformation of sulfur and carbon in the sediment of sanitary sewer. (1st May 2015) - Liu, Yanchen; Wu, Chen; Zhou, Xiaohong; Zhang, Tuanjie; Mu, Lei; Shi, Hanchang
Abstract: This study aims to estimate the influence of the typical variation in liquid conditions on the biochemical reaction characteristics of sulfur and carbon in the sediment of gravity sanitary sewers. Thus, a series of experimental tests were conducted with real wastewater and sewage sediment to investigate the potential biochemical process of carbon and sulfur in sediment. Results indicated that the sulfur and carbon biochemical process in sediment with neutral pH is significant in the gravity sewage system. The changes in concentration and the ratios of wastewater component substrates are the key factors in chemical oxygen demand and sulfate reduction rates. Furthermore, the condition of dissolved oxygen in liquid significantly affected the biochemical reaction processes of sulfur and carbon. Finally, the frequent alternation of anaerobic and anoxic with low dissolved oxygen effectively inhibits sulfide accumulation and simultaneously reduces carbon loss in the sewage system. Highlights: Carbon and sulfur biochemical process in sewer sediment was investigated. DO condition significantly determines the VFA and sulfide accumulation. Low COD/SO4 2− ratio and DO limit the loss of readily biodegradable substrate. Frequent alternation of anaerobic/anoxic effectively inhibits sulfide accumulation.